Bioactive isoquinoline alkaloids from Glaucium arabicum. (December 2018) - Elbermawi, Ahmed; Sallam, Amal; Ghabbour, Hazem A.; Elsebai, Mahmoud F.; Lahloub, Mohamed F.; Saad, Hassan-Elrady A.
Graphical abstract: Highlights: The aerial parts of Glaucium arabicum were phytochemically investigated. Two new isoquinoline alkaloids (compounds 1 and 2) were isolated and identified on the basis of spectroscopic methods. Melanin synthesis inhibitory activity was evaluated for the isolated isoquinoline alkaloids. Abstract: Phytochemical investigation of the aerial parts of Glaucium arabicum Fresen. (Papaveraceae) led to the isolation of two previously undescribed isoquinoline alkaloids araglaucine A, and araglaucine B, together with seven known ones 1-[(3`, 4`-dimethoxy-2`-methylcarboxy)benzoyl]-6, 7-methylenedioxy isoquinoline (araglaucine C), (7 R, 14 S )- trans - N -methylcanadinium nitrate, ( R, S )- trans - N -methylstylopine, 14-hydroxy -N- methyl canadine, 14-hydroxy -N- methyl stylopine, protopine, norsanguinarine, as well as β -sitosterol, and β -sitosterol 3- O - β –d -glucoside. Their structural elucidation was based on the measurements of 1D, 2D NMR, HRESIMS, UV, IR and X-ray crystallography. The compounds were evaluated for their anti-melanogenesis activity using B16 melanoma cell lines. Compound (7 R, 14 S )- trans - N -methylcanadinium nitrate exhibited a promising melanin synthesis inhibitory activity (∼35%) at concentration 5 μg/ml (12.01 μM) with low cytotoxicity (∼12%).